Proliferating cell nuclear antigen and S phase fraction in endometrial stromal sarcoma. Issue 8 (August 1992) - Schofield, J B; Mansi, J; Camplejohn, R S; Lane, D P; Fisher, C
Abstract : AIMS: To investigate the value of immunohistochemical staining for the cell cycle protein proliferating cell nuclear antigen (PCNA) and flow cytometric S phase fraction in determining prognosis in endometrial stromal sarcoma, graded according to mitotic count. METHODS: Seventeen endometrial stromal sarcomas from 13 patients treated at the Royal Marsden Hospital were analysed. Serial 5 microns sections were cut for haematoxylin and eosin and immunohistochemical staining for PCNA, performed using the murine monoclonal antibody PC10. PCNA positivity was expressed as a percentage of the total number of cells (PCNA index). Flow cytometric analysis was performed on nuclei extracted from paraffin wax sections. RESULTS: In the five patients who died of disease within five years, PCNA index varied between < 1% and 60% (mean 21%) and S phase fraction ranged from 11.3 and 20.1 (mean 13.8). Four patients who were apparently cured showed PCNA indices ranging from < 1% to 5% (mean 1.75%) and S phase fraction ranging from 1.4 to 3.5 (mean 2.3); and three patients alive with disease showed PCNA indices ranging from 1% to 15% (mean 8.6%) and S phase fraction ranging from 1.4 to 3.5 (mean 2.3). One patient who died from indolent local disease after nine years showed a PCNA of 1 or less and an S phase fraction of 0.9. CONCLUSIONS: PCNA staining was variable and therefore not a reliable prognostic indicator, but a high PCNA index was only found in those patients dying of disease within five years. A stronger association was seen between S phase fraction and prognosis; this also correlated well with histological grade determined by mitotic count. In individual borderline cases that are between low and high grade categories, these procedures may be useful.